Recurrence of Idiopathic Granulomatous Mastitis Following Treatment With Oral Prednisolone - Akter, Sadia; Ahmed, Shakera; Mostafa, Faisal; Abedin, Mohammad Ahsanul; Palit, Liton Kumar; Paul, Balaram (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Idiopathic Granulomatous Mastitis (IGM) isn't very uncommon persistent inflammatory disorder of the breast. IGM treatment is still a debate. presently, no universally accepted treatment method is available. The complete remission/resolution and recurrence rates of prednisolone treatment reported in currently available studies varied. In this context, We have conducted this prospective study to evaluate the recurrence rates of prednisolone therapy for the patients with IGM. To investigate the impact of oral Prednisolone on recurrence of IGM. Materials and methods: This hospital based prospective observational study was conducted at Department of Surgery, Chittagong Medical College Hospital (CMCH) for one year period from January 2019 to December 2019. A total 150 case of IGM with histological diagnosis were selected purposively from Surgery Department of CMCH .Treatment protocol included oral Prednisolone at a dose of 1mg/kg/day for 1 month followed by tapering of the doses over next 1 month. Patients were assessed 2 months and 6 months after treatment completion for reappearance of lump, change in pain and skin conditions from baseline. Results: Mean of age 29.67 (± 5.67) years and ranges between 20 and 48 years. The maximum not unusual presenting signs and symptoms have been a mass in the breast and ache. Majority of the lump (74%, 111/one hundred fifty) had been positioned within the top and outer quadrant of the breast. Skin ulcer and sinus was present in only 4% and 5.3% cases respectively. Out of 150 cases 47 (31.3%) had recurrence. Size and extent of the breast lump of the recurrent cases were smaller than the initial breast lump. Pain intensity varies in nature during initial and recurrent presentation. There was no axillary lymph node involvement or skin ulcer in the recurrent cases. Conclusion: Prednisolone therapy was effective in the treatment of IGM as evident by low recurrence rate. JCMCTA 2025 ; 36 (1) : 119-123